La Problématique D’intégration Des Migrants Ressortissants Du Rwanda Et Du Burundi En République Démocratique Du Congo - Munenge Mudage Florent; Mangaiko Mudage Lebon (European Scientific Journal, ESJ, 2018)
This article critically diagnoses the integration difficulties encountered by Rwandan and Burundian immigrants in the Democratic Republic of Congo since 1960. Main treatments, xenophobic, and discriminatory practices used against the nationals of these two countries by indigenous Congolese people were analyzed in terms of obstacles to integration. The article also scrutinizes the derogatory, hegemonic, and disdainful behavior and attitudes of these immigrants towards the host society. The problems that these immigrants have to face from the authorities of the host country in the application of national migration policies were analyzed. Also, the way they were led into a clandestine life into the host country was also studied. The article, however, aims to reveal socio-cultural, political, and legal challenges which plague the daily life of Rwandan and Burundian nationals who have chosen the DRC as their second homeland.